Neuronal response of the primate striatum tail to face of socially familiar persons - Jun Kunimatsu; Hidetoshi Amita; Okihide Hikosaka (iScience, 2024)
Summary: Recent studies have suggested that the basal ganglia, the center of stimulus-reward associative learning, are involved in social behavior. However, the role of the basal ganglia in social information processing remains unclear. Here, we demonstrate that the striatum tail (STRt) in macaque monkeys, which is sensitive to visual objects with long-term reward history (i.e., stable object value), is also sensitive to socially familiar persons. Many STRt neurons responded to face images of persons, especially those who took daily care of the subject monkeys. These face-responsive neurons also encoded stable object value. The strength of the neuronal modulation of social familiarity and stable object value biases were positively correlated. These results suggest that both social familiarity and stable object value information are mediated by a common neuronal mechanism. Thus, the representation of social information is linked to reward information in the STRt, not in the dedicated social information circuit.